A CURRICULUM FRAMEWORK FOR GEOGRAPHICAL INFORMATION SCIENCE (GISc) TRAINING AT SOUTH AFRICAN UNIVERSITIES - du Plessis, Heindrich (South African Journal of Higher Education, 2016)
Geographical information science (GISc) is one of the fastest growing industries worldwide. Being a relatively new discipline, universities often provide training as part of geography, surveying, town planning, environmental and computer science programmes. This complicates professional accreditation assessments as the content, outcomes, extent and quality of training can vary significantly. In this paper one international and two South African GISc curriculum development models are qualitatively compared. Results show that, although there is significant intersection between the three models, some characteristics are unique to specific models. A new framework consisting of 15 components and compatible with international curricula is proposed. It addresses the needs of the South African industry while meeting the requirements of the South African GISc professional registration body. It is furthermore useful for comparing curricula and can support general curriculum design. Keywords curriculum development; geographical information science (GISc); geomatics; geographical information systems (GIS); training; programme accreditation